c - Burdett (Archive Editions Ltd, 2004)
The events of the period 1966 to 1971 reveal a tumultuous period in the history of Saudi Arabia: the exile of King Saud; the war with Yemen over Asir and other disputed territories; the concerns for security engendered simultaneously by aggression from the UAR in support of Yemeni insurgents and from the Arab-Israeli War of 1967; unresolved territorial contests with other Gulf states; the implications for the region of the dramatic decision of the British to withdraw firstly from Aden, then from the Gulf, by 1971; and increasingly complex negotiations over petroleum rights through OPEC. However, by the close of this period several boundary agreements were reached; more positive relations with neighbouring states, including Egypt, were consolidated, partly through aid and partly by the Saudi desire to fill the power vacuum left by the end of the British presence; and the war with Yemen was concluded.